The Corbusian suspended garden : a fragment of nature converted into architecture - Suárez, María Candela (2014)
In Le Corbusier’s work it is possible to tie the projects to common factors. One of these is the series of residential single-family homes and multiple families homes or apartments, which share one element of formal spatial function: the suspended garden. These elements act as an air capsule that transforms the limit of the façade, by dilating the transition between the public and the private, interior and exterior, architecture and nature. In this paper I refer to Le Corbusier in relation to the nature, which he referred to as the “antagonist”. I enquire into the genesis of the suspended garden – a connector of space used by Le Corbusier to connect himself with “the antagonist”, or the natural greenspace. To reinforce the ideas about the suspended garden, I offer some latent references to interior/exterior space that, even if they are not a consciously recreated by Le Corbusier, they are “reactive,” useful to reveal some attributes either formal, spatial or symbolic – that could form part of his intentions for the project. One of the references, already remarked by other authors, is the Cartusian monastery cells. Another are the gardens of Balkan houses, the medieval enclosed gardens, and the Persian paradise garden.